Pressure Sensor Devices Featuring a Chemical Passivation Made of a Locally Synthesized Diamond Layer. Issue 4 (27th October 2022) - Bähr, Mario; Käpplinger, Indira; Pobedinskas, Paulius; Frank, Thomas; Grün, André; Haenen, Ken; Ortlepp, Thomas
Abstract : The rear side of a pressure sensor diaphragm is prepared with an additional diamond layer as protective coating against harsh media. The preparation sequence for the diamond coating is developed as a simple backend process, combining only two additional steps in the standard process. These are the local seeding of nanodiamond layer and the low‐temperature diamond growth at <300 °C in a linear antenna microwave plasma‐enhanced chemical vapor deposition reactor, where only at the nanodiamond seeded sites, a high‐quality diamond film was synthesized. The seeding resolution in the setup used was limited to ≈80 μm, but can be further reduced. In an industry‐typical assembly sequence the diamond coated pressure sensor devices are further equipped with a support wafer and mounted to a TO‐8 socket. Tests of such sensor systems indicate that the diamond layer does not hamper the stability of the device. This proofed method of postprocessing an only‐local and low‐temperature synthesis of a diamond layer on the wafer‐level opens‐ up possibilities for many other applications, since this approach is scalable and in general cost effective. Abstract : The rear side of a pressure sensor diaphragm is prepared with a diamond layer as protective coating against harsh media. Diamond manufacture is developed as a backend‐process, combining the local seeding of nanodiamond and the low‐temperature diamond growth at <300 °C, without additional structuring. In an industry‐typical assembly sequence, diamond‐coated pressure sensors are set up and tested.